KEBIJAKAN SOSIAL BERBASIS NILAI BUDAYA: PENDEKATAN SYSTEMATIC LITERATURE REVIEW (SLR) - Putra, Ronny Ersya Novianto; Ikhwaningrum, Dian Utami (CERMIN: Jurnal Penelitian, 2025)
Social policy is a crucial instrument for addressing inequality and improving community welfare. However, its effectiveness largely depends on the sociocultural context surrounding the target community. This systematic literature review aims to analyze how cultural values are integrated into social policies, implementation models, obstacles, and their impact on social sustainability. The study employs a Systematic Literature Review (SLR) approach by analyzing at least 15 reputable international journals published between 2017 and 2023. The findings reveal that culture-based social policies enhance legitimacy, community participation, and program effectiveness, despite challenges such as bureaucratic resistance and cultural diversity complexity. Policy implications emphasize inclusive mechanisms, cultural sensitivity training, and stakeholder synergy to ensure successful, sustainable, and inclusive social policy.